Key Economic Characteristics of Italian Trawl Fisheries and Management Challenges - Sabatella, Evelina C.; Colloca, Francesco; Coppola, Gianluigi; Fiorentino, Fabio; Gambino, Monica; Malvarosa, Loretta; Sabatella, Rosaria (Frontiers in Marine Science, 2017)
Two key measures of economic performance are calculated and analyzed for three important Italian trawl fisheries (Northern Thyrrenian Sea, South of Sicily, Northern Adriatic Sea): the Net Economic Returns (NER), which informs on the economic performance and is considered a proxy of resource rent in fisheries and the Return on Fixed Tangible Assets (ROFTA), which is used as an approximation of the Return on Investment (ROI) and is a key financial and performance indicator for a fisherman in order to take a decision to operate in a fishery. The trend of these indicators over the last decade highlights a poor economic performance that is associated with an overall poor condition of the state of resources. The trend of economic performance indicators is put in relation, on a time-based approach, with the different types of management measures applied over the last decade. We show that trends of fishing effort and economic indicators as well as statistical analysis return a coherent interpretation of the main factors affecting the profitability levels of the selected fleets. The study reveals that management measures impacted negatively on the profitability of the sector in the short run. However, economic indicators inverted the trend in the last 3 years. An increasing biomass trend as well as the improvement in fishing mortality of some few stocks, together with the reduction of input costs could be considered as positive drivers which impacted positively on economic profitability of the fisheries concerned. The study argues that even the technical and fishery management provisions in the Mediterranean Sea may have started to reverse the trend in economic profitability of the analyzed fleets. An additional management effort needs, however, to be developed on an urgent basis in order to ensure the achievement of the management goals defined by the Common Fisheries Policy (CFP).